Terapi Bermain Melipat Origami Untuk Meningkatkan Motorik Halus Pada Anak Berkebutuhan Khusus - Safrudin, M. Bachtiar; Widyastuti, Dwi; Sadien, Rayshifa; Safitri, Dwi Amelia; Anggreini, Niken; Putri, Anisa Duwi (Innovative: Journal Of Social Science Research, 2025)
Children with special needs require a learning and therapy approach that is tailored to their characteristics, especially in the development of fine motor skills. This study aims to analyze the effectiveness of origami folding play therapy in improving the fine motor skills of children with special needs at SLBN Samarinda City. This activity was carried out through three stages, namely preparation, implementation, and evaluation, involving 10 students. The results showed that this therapy helped to improve students' hand-eye coordination, accuracy, and concentration. In addition, this therapy also contributes to cognitive and social aspects, such as improving interaction and understanding instructions. Thus, origami folding play therapy can be an alternative method in the education of children with special needs. In the future, this therapy can be further developed with a variety of more complex origami shapes and a more personalized approach.